BUSSINES MODEL CANVAS SEBAGAI ALTERNATIF STRATEGI BISNIS KERAJINAN SEDOTAN PURUN DI DESA TUMBANG NUSA, KECAMATAN JABIREN KABUPATEN PULANG PISAU - Daniel Itta; Muhammad Helmi; Adnan Ardhana (Lambung Mangkurat University-Indonesia, 2021)
This study aims to analyze the business model of the purun straw craft business in Tumbang Nusa Village and determine the strategy for developing the purun straw craft business model in Tumbang Nusa Village with the Bussines Model Canvas (BMC) approach. Purun straws in Tumbang Nusa village. This study uses descriptive research methods to collect detailed actual information that describes existing symptoms, identifies problems or examines prevailing conditions and practices. The results of the research on the canvas model business mapping that have been carried out, it turns out that the customer segment of the purun straw craftsmen has been diversified into Bussines to Bussines and Bussines to Consumer customers with marketing reach in the cities of Palangkaraya, Jakarta and Bali. The revenue stream element from straw craftsmen is only in the form of selling straws. Furthermore, the main resources used are production equipment, human resources, capital, transportation and communication tools with key activities in the form of production and marketing activities. Meanwhile, the main partnership that keeps the business running is the Liaison and the government. The last element in the form of a cost structure contains fixed costs and variable costs. After getting information from the business model environment and SWOT analysis, the changes to the existing canvas business model are obtained. In order for the production process to run more efficiently, the use of appropriate technology is added through production mechanization, while for the main activity promotional activities are added. Researchers suggest craftsmen can implement improvement strategies on the Business Model Canvas elements that focus on five elements, namely, Customer segments, Channels, Customer relationships, Key activities and Key partners so that operational activities are expected to be more effective